2021
DOI: 10.4293/jsls.2021.00019
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Transvaginal and Transumbilical Laparoscopic Single-Site Surgery for Ovarian Cysts

Abstract: Background: Minimally invasive surgery is currently a preferred treatment for symptomatic ovarian cyst(s), with single-site techniques, such as transumbilical laparoendoscopic single-site surgery (TU-LESS) and transvaginal laparoendoscopic single-site surgery (TV-LESS), gaining increasing popularity. Although both methods have delivered positive outcomes, there is currently limited literature directly comparing TU-LESS and TV-LESS.Objectives: This study had two primary objectives: (1) to evaluate the safety an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(21 citation statements)
references
References 18 publications
5
15
1
Order By: Relevance
“…3,21 However, a previous study did not find a difference in surgical time between vNOTES and LESS. 22 In agreement with previous studies, our study also found that the vNOTES OC had a shorter surgical time than LESS.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…3,21 However, a previous study did not find a difference in surgical time between vNOTES and LESS. 22 In agreement with previous studies, our study also found that the vNOTES OC had a shorter surgical time than LESS.…”
Section: Discussionsupporting
confidence: 93%
“…19 Another study did not find a difference in blood loss between NOTES and LESS. 3,22 However, our study showed less blood loss in vNOTES than in LESS.…”
Section: Discussioncontrasting
confidence: 50%
See 2 more Smart Citations
“…However, with the deepening of the concept of minimally invasive surgery, many young patients are not only satisfied with retaining fertility, but also pursuing cosmetic needs [ 5 ]. Today, laparoendoscopic single-site myomectomy (LESS-M) is increasingly concerned, as it is less invasive than conventional three- and four-port surgery, which is conducive to patients' rapid recovery with better cosmetic effects [ 6 , 7 ]. However, there is currently a paucity of comparative studies on LESS-M and MLS-M in patients with UFs, resulting in the insufficiency of evidence-based medicine evidence for its application effect and safety in the disease.…”
Section: Introductionmentioning
confidence: 99%